Neoadjuvant Chemotherapy with Laser Interstitial Thermal Therapy in Central Nervous System Neuroblastoma: Illustrative Case and Literature Review - Jason E. Chung; Omar Iqbal; Chandra Krishnan; Virginia Harrod; Elizabeth Tyler-Kabara; Rongze O. Lu; Winson S. Ho (Brain Sciences, 2023)
Primitive neuroectodermal tumors of the central nervous system, or CNS neuroblastoma, are rare neoplasms in children. Recently, methylation profiling enabled the discovery of four distinct entities of these tumors. The current treatment paradigm involves surgical resection followed by chemotherapy and radiation. However, upfront surgical resection carries high surgical morbidity in this patient population due to their young age, tumor vascularity, and often deep location in the brain. We report a case of CNS neuroblastoma that can be successfully treated with neoadjuvant chemotherapy followed by minimally invasive laser interstitial thermal therapy and radiation. The patient has complete treatment with no evidence of recurrence at one year follow-up. This case illustrates a potential paradigm shift in the treatment of these rare tumors can be treated using minimally invasive surgical approach to achieve a favorable outcome.